Respons dan Tantangan Kaum Tua atas Kritik Kaum Muda terhadap Tarekat di Minangkabau Awal Abad 20 - Nasrullah Nasrullah (Institut Ilmu Keislaman Annuqayah, 2016)
This paper is a discription of the debate over the issue of legitimacy of tarekat in the Minangkabau region in the early 20th century between the old traditionalist ulama and the young modernist ulama. The theoretical framework used to analyze the problem above is the theory of challenge and response by the historian Arnold J. Toynbee. The theory is about the dialectics of history and culture due to the causality of the challenges and responses, both in ideas, discourse and movement. The importance of this theory is to answer the fundamental issue about the meaning of tarekat from the perspective of the two groups of ulama along with the things underlying these differences.The conclusions in response to the problem is that the tarekat institution (Naqsyabandiyah-Khalidiyah) with it various form of practice such as geneology, rabitah, suluk, avoid from eating meat and so in the view of the old ulama is the result of ijtihad of the sufi scholars taken from the Quran and Hadis teachings as a way to get closer to the God, while according to the youth ulama, the tarekat practice above are not based totally on the guidance of the Quran and the Hadis. Therefore, regarded as heretical act category. But the youth did not oppose the amali and salafi practice of sufisme with a very tight relationship sufism and sariah.